2022
DOI: 10.1159/000520672
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Algorithms as a Computer-Assisted Decision Tool for Oral Cancer Prognosis and Management Decisions: A Systematic Review

Abstract: <b><i>Introduction:</i></b> Despite multiple prognostic indicators described for oral cavity squamous cell carcinoma (OCSCC), its management still continues to be a matter of debate. Machine learning is a subset of artificial intelligence that enables computers to learn from historical data, gather insights, and make predictions about new data using the model learned. Therefore, it can be a potential tool in the field of head and neck cancer. <b><i>Methods:</i></b&g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…All the articles included in this review were published in English. Of the 17 included systematic reviews [ 1 , 5 , 7 , 13 26 ], 11 were conducted in Europe [ 1 , 5 , 7 , 14 , 15 , 17 19 , 21 , 22 , 24 ] while 4 were conducted in Asia [ 16 , 23 , 25 , 26 ] and 2 in the United States [ 13 , 20 ] (Table 2 ). All but one of the included systematic reviews showed high-quality appraisal and low risk of bias (Tables 3 , 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the articles included in this review were published in English. Of the 17 included systematic reviews [ 1 , 5 , 7 , 13 26 ], 11 were conducted in Europe [ 1 , 5 , 7 , 14 , 15 , 17 19 , 21 , 22 , 24 ] while 4 were conducted in Asia [ 16 , 23 , 25 , 26 ] and 2 in the United States [ 13 , 20 ] (Table 2 ). All but one of the included systematic reviews showed high-quality appraisal and low risk of bias (Tables 3 , 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…All but one of the included systematic reviews showed high-quality appraisal and low risk of bias (Tables 3 , 4 ). Seven of the systematic reviews were conducted in the year 2021 [ 1 , 5 , 16 20 ], 6 in 2022 [ 21 26 ], and the remaining 4 before the year 2021 [ 7 , 13 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…These limitations included a limited amount of data available, the retrospective collection of data, image quality, the comparison of images taking into consideration that healthy tissue could be present with mucosal alterations, imbalances in the data used to train, the risk of missing data, the lack of studies collaborating with clinical diagnosis and biopsy findings, the task of automation, infrastructure requirements for data storage, building and training AI models, and patient privacy and ethical issues. 3 , 39 …”
Section: Discussionmentioning
confidence: 99%
“…[38] Chiesa-Estomba et al analyzed eight studies and concluded that machine learning (ML) had the potential to considerably advance the field of OC research due to the ability of ML models to constantly learn with additional data. [39] J o u r n a l P r e -p r o o f 9…”
Section: Ai In Oral Cancer Screening and Detectionmentioning
confidence: 99%
“…Both the management in the treatment of oral carcinoma patients and the predictions and forecasts could be significantly improved. The prerequisite for this is to improve and democratise the use of algorithms [ 10 ].…”
Section: Future Challenges and Innovative Strategies – Perspectives I...mentioning
confidence: 99%